2021
DOI: 10.1007/jhep10(2021)086
|View full text |Cite
|
Sign up to set email alerts
|

EFT at FASERν

Abstract: We investigate the sensitivity of the FASERν detector to new physics in the form of non-standard neutrino interactions. FASERν, which will be installed 480 m downstream of the ATLAS interaction point, will for the first time study interactions of multi-TeV neutrinos from a controlled source. Our formalism — which is applicable to any current and future neutrino experiment — is based on the Standard Model Effective Theory (SMEFT) and its counterpart, Weak Effective Field Theory (WEFT), below the electroweak sca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 100 publications
0
23
0
Order By: Relevance
“…From the reactor neutrino experiments Daya Bay and RENO and taking into account the EFT effect on nuclear beta and inverse beta decay interactions we can get constraints on the right handed, scalar and tensor interactions using the νe → νe transition: [ ud R ] eµ,eτ ∼ (0.05−0.1), where X = R, S, T [96]. Using the same approach the SMEFT coefficients were studied at the FASERν detector at LHC, where new physics effects on the neutrino production through meson decays and neutrino detection through Deep Inelastic Scattering (DIS) were studied [98]. It was shown that FASERν detector has the capability to constraint new physics at the multi-TeV scale, for some 4-fermion interactions giving constraints that are much better than the existing constraints in the literature (see e.g.…”
Section: General Effective Interactions Between Neutrinos: the Charge...mentioning
confidence: 99%
“…From the reactor neutrino experiments Daya Bay and RENO and taking into account the EFT effect on nuclear beta and inverse beta decay interactions we can get constraints on the right handed, scalar and tensor interactions using the νe → νe transition: [ ud R ] eµ,eτ ∼ (0.05−0.1), where X = R, S, T [96]. Using the same approach the SMEFT coefficients were studied at the FASERν detector at LHC, where new physics effects on the neutrino production through meson decays and neutrino detection through Deep Inelastic Scattering (DIS) were studied [98]. It was shown that FASERν detector has the capability to constraint new physics at the multi-TeV scale, for some 4-fermion interactions giving constraints that are much better than the existing constraints in the literature (see e.g.…”
Section: General Effective Interactions Between Neutrinos: the Charge...mentioning
confidence: 99%
“…Using CCQE as a signal channel, one could probe flavor-dependent structures. This idea is discussed within the context of non-standard interactions and SM effective field theory (SMEFT) in [201,202]. Projections in [201] rely on charged-current to neutral-current cross section ratios σ CC /σ NC , and explicitly neglect uncontrolled theoretical uncertainties related to argon's complex nuclear structure and non-zero isospin.…”
Section: Modifications To Neutino-nucleon Cross Sectionsmentioning
confidence: 99%
“…FASERν is primarily designed for the purpose of identifying the flavors of neutrinos [38,39], the discovery potential of FASERν for new physics discussed in [40][41][42][43]. The expected sensitivity for each flavor at FASERν is shown in figure 6.…”
Section: Jhep12(2021)209mentioning
confidence: 99%